HIV Viremia During Pregnancy and Neurodevelopment of HIV-Exposed Uninfected Children in the Context of Universal Antiretroviral Therapy and Breastfeeding: A Prospective Study. Issue 1 (January 2019) - le Roux, Stanzi M.; Donald, Kirsten A.; Kroon, Max; Phillips, Tamsin K.; Lesosky, Maia; Esterhuyse, Liza; Zerbe, Allison; Brittain, Kirsty; Abrams, Elaine J.; Myer, Landon
Abstract : Background: Elevated HIV viral load (VL) in pregnancy has been linked to increased risk of mortality, immunologic abnormalities, infectious morbidity and restricted growth among HIV-exposed uninfected (HEU) children, but little is known about effects on child development. Methods: HIV-infected women initiating lifelong antiretroviral therapy (ART; tenofovir + emtricitabine + efavirenz) antenatally were followed from first antenatal visit through delivery and with their breastfed infants postpartum. Cognitive, motor and expressive language development (Bayley Scales of Infant and Toddler Development-Third Edition; delay defined as score <85) were assessed on a subset of HEU infants. HIV VL was measured at ART initiation, in third trimester and around delivery. Cumulative viremia in pregnancy was expressed as log10 VL copies × year/mL [viremia copy-years (VCY)]. Relationships between VCY and development were examined after adjusting for socioeconomic, behavioral and psychosocial confounders. Results: Women (median pre-ART log10 VL 4.1, CD4 349 cells/mm 3 ) commonly reported adverse social circumstances (44% informal housing, 63% unemployed, 29% risky drinking). Among 214 infants (median age, 13 months; 53% male; 13% born <37 weeks' gestation), viremia predicted lower motor and expressive language, but not cognitive, scores in crude and adjusted analysis [per log10 VCY increase, αβ (95% confidence interval [CI]): motor, −2.94 (−5.77 to −0.11); language, −3.71 (−6.73 to −0.69) and cognitive −2.19 (−5.02 to 0.65)]. Increasing VCY also predicted higher relative odds of motor delay [adjusted odds ratio (aOR): 3.32; 95% CI: 1.36–8.14) and expressive language delay (aOR: 2.79; 95% CI: 1.57–4.94), but not cognitive delay (aOR: 1.68; 95% CI: 0.84–3.34). Conclusions: Cumulative maternal HIV viremia in pregnancy may have adverse implications for HEU child development. Abstract : Supplemental Digital Content is available in the text.